Collaborative Learning with Augmented Reality Tornado Simulator - Chiou, Yan-Ming; Shen, Chien-Chung (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
Research has shown that AR can improve learning with better content understanding. In addition, collaborative learning has shown to increase motivation and improve learning performance. Using the subject of tornado, the paper describes the design of a multi-user augmented reality tornado simulator using Unity to facilitate collaborative learning. Students working in pairs first set up a village and configure the funnel width, pressure difference, and rotation speed of a tornado and then watch the tornado whipping through the village to destroy properties on Apple iPads. To evaluate the performance of collaborative learning, 22 sixth-grade students were recruited into control and experimental groups, whose learning performance was measured with pre and post tornado knowledge test questionnaires. The results demonstrate a significant performance improvement with collaborative learning.